2022
DOI: 10.3390/ma15072700
|View full text |Cite
|
Sign up to set email alerts
|

Designing Carbon-Enriched Alumina Films Possessing Visible Light Absorption

Abstract: Aluminum anodization in an aqueous solution of formic acid and sodium vanadate leads to the formation of alumina/carbon composite films. This process was optimized by varying the concentrations of formic acid and sodium vanadate, the pH, and the processing time in constant-voltage (60–100 V) or constant-current mode. As estimated, in this electrolyte, the anodizing conditions played a critical role in forming thick, nanoporous anodic films with surprisingly high carbon content up to 17 at.%. The morphology and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…41 It was also shown that aluminum anodization in an aqueous solution of formic acid with the additive of sodium vanadate leads to forming of porous alumina films. 10 In this case, vanadate ions prevented initial corrosion, and the film with a thickness of about 40 μm was formed at 80 V in 1 h. For anodizing in formic acid with ammonium heptamolybdate additive, the situation is very similar, i.e., porous alumina with a thickness of about 20 μm is formed at 80 V in 1 h. The only difference observed is the absence of the ordered porous structure and the presence of the dense, cracked cover layer on the film surface (See Figs. 2A-2C).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…41 It was also shown that aluminum anodization in an aqueous solution of formic acid with the additive of sodium vanadate leads to forming of porous alumina films. 10 In this case, vanadate ions prevented initial corrosion, and the film with a thickness of about 40 μm was formed at 80 V in 1 h. For anodizing in formic acid with ammonium heptamolybdate additive, the situation is very similar, i.e., porous alumina with a thickness of about 20 μm is formed at 80 V in 1 h. The only difference observed is the absence of the ordered porous structure and the presence of the dense, cracked cover layer on the film surface (See Figs. 2A-2C).…”
Section: Resultsmentioning
confidence: 99%
“…44,47 At the same time, a large number of bubbles formed during anodizing can change the current distribution on the surface of the oxide film, leading to a lower heat transfer rate between the electrolyte and the reaction surface. Moreover, HCOOH species are also absorbed in the growing alumina and can be decomposed in one of the possible ways 10,48 resulting in CO and CO 2 formation. Additionally, due to local overheating, they can also disproportionate into a-C:H through dissociative adsorption, decarboxylation, dehydrocyclization, and polycondensation reactions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14] Electrolytes based on a formic acid solution with vanadate and heptamolybdate additives were used to obtain carbon-enriched alumina composites with an average carbon content of ca. 5.5 mass%, and the carbon embedded in the alumina in the form of CO 2 , CO, carboxylate ions, and a-C:H. 15,16 In these solutions, the anodizing process was non-steady, leading to the generation of nonuniform current pathways, resulting in the formation of a hierarchical structure with multi-branched pores. However, the films had hillocks and were covered with cracks.…”
mentioning
confidence: 99%